Using and sharing information on social media by high school students: a case study of a private school in Sao Paulo state - Paulo, Rodrigo Barbosa de [UNESP]; Silva Casarin, Helen de Castro [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2021)
The behavior of high school students in the use of the internet and social media was identified and their perception of the posture of parents or guardians. The study was conducted with students from a private school located in Sao Paulo state. For data collection, an electronic questionnaire was applied, which was distributed to 279 students, covering all students in the eight high school classes, and a total of 216 valid responses (77,4% of the total) were obtained. The results obtained demonstrate that 98,0% of the students participating in the study use some social network; 71,0% of respondents said they had received images with sexual content and access to these materials was mainly through social networks. The subject with the highest incidence of search among respondents was on weight loss diets. 71,0% of students who answered the questionnaire considered that they know more about the internet than their parents. The main conclusion of this study is that, given the finding that adolescents have adopted risky behavior in the use of social networks and have not received adequate guidance in this regard, the school has a fundamental role in preparing students to deal safely with the informational universe to which they have daily access.
Keywords: Information security; Social media; Information literacy; Teenagers; User studies